Coerced Labour, Forced Displacement, and the Soviet Gulag, 1880s-1930s - Popova, Zhanna 1989- (Social History of Punishment and Labour Coercion, 2024)
The Gulag remains one of the key symbols of twentieth-century mass political violence. Thanks to recent archive-based investigations, we now understand the scope of the system, variations between different camp complexes, and modalities of the use of forced labour of convicts. At the same time, the work of historicizing the Gulag and systematically evaluating its position within the global history of repression is still to be done. Exploring the emergence of this vast Soviet system of concentration camps in long-term perspective, this book aims to inscribe this process within global histories of coerced labour, forced displacement, and punishment. It highlights the inextricable interconnection of coerced labour and forced displacement as tools of punishment in the multitude of their historical forms.